2015
DOI: 10.5937/ratpov52-7723
|View full text |Cite
|
Sign up to set email alerts
|

Bulb fresh weight mode of inheritance in onion (Allium cepa L.)

Abstract: Summary:One of the most important traits of onion bulb is its bulb fresh weight. Also, this trait is in a group of morphological markers that, together with RAPD, represent the parameter of the most precise identification of onion genotype. For the purpose of this study, the chosen genotypes were: Makoi bronzi, Piroska, AC 101, Jasenicki crveni, Bukino beo. Also, they were of a different geographical origin. Method of full diallel without reciprocals was applied in order to obtain F1 and F2 generation. Field t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…Our results are supported by the findings of Gulumbe et al (2018). Results for bulb yield were supported by the studies of Pavlović et al(2015). From the present results of heterosis and heterobeltiosis, four combinations were observed with maximum values for bulb yield and its contributing traits.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are supported by the findings of Gulumbe et al (2018). Results for bulb yield were supported by the studies of Pavlović et al(2015). From the present results of heterosis and heterobeltiosis, four combinations were observed with maximum values for bulb yield and its contributing traits.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results in its researches were found by PAVLOVIĆ, (1999); PAVLOVIĆ et al, (2003); HAYDAR et al, (2007). Similar values for heritability of bulb height in its research were confirmed by RAJALINGAM and HARIPRIYA, (1998); MOHANTY et al, (2001a); SINGH et al, (2010); PAVLOVIĆ et al, (2003); PAVLOVIĆ et al, (2015).…”
Section: Graph 3 Ammi 1 Biplot For Total Yield Of 10 Onion Genotypessupporting
confidence: 78%
“…The main component of onion yield is the bulb mass that together with plant density per area unit has a direct impact. Bulb mass is a morphological marker and represents the variety trait impacted by edaphic and ecological factors (PAVLOVIĆ et al, 2002;PAVLOVIĆ et al, 2012;PAVLOVIĆ et al, 2015). Bulb height directly determinates its form, which impacts the usage of onion bulbs (markets, industrial proceeding), market value, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Bulb weight and the realized bulb set per unit area are the components that directly determinate onions yield, implying the importance of the traits for both breeders and producers (PAVLOVIĆ et al, 2015). According to the analysis of variance of AMMI model for onion bulb weight and number plot -1 harvested from the conventionally and organically maintained plots in the two-year field trial, all sources of variation were highly significant (Table 1, 2).…”
Section: Resultsmentioning
confidence: 99%